The relationship between economic growth and biomass energy consumption in some European countries - Bildirici, Melike E.; Ozaksoy, Fulya (AMER INST PHYSICS, 2013)
In this paper, the causality analysis between biomass energy consumption and economic growth was investigated in the selected 10 countries by using Autoregressive Distributed Lag bounds testing approach and vector error-correction models. Annual data cover the period from 1960 to 2010. The short run, long run, and strong causality results suggest that there is unidirectional causality from Y to biomass energy consumption for Austria and Turkey, and there is unidirectional causality from biomass energy consumption to Y for Hungary and Poland. For Spain, Sweden, and France, it was found as bidirectional causality. According to strong and long run causalities, bidirectional causality was found for all the countries. (C) 2013 AIP Publishing LLC. [http://dx.doi.org/10.1063/1.4802944]
Keywords: BIOENERGY; POLICY; GNP; Science & Technology - Other Topics; Energy & Fuels